Detection and Phylogenetic Analysis of Alphacoronaviruses in Bat Populations of Rostov and Novosibirsk Regions of Russia, 2021–2023 - Olesia V. Ohlopkova; Igor V. Popov; Ilia V. Popov; Kristina A. Stolbunova; Marina A. Stepanyuk; Alexey D. Moshkin; Aleksei A. Maslov; Ivan A. Sobolev; Aleksey V. Malinovkin; Elizaveta V. Tkacheva; Daria A. Bogdanova; Ekaterina A. Lukbanova; et al. (Microbiology Research)
Bats are natural reservoirs for many emerging viruses, including coronaviruses that were probably progenitors to human coronaviruses with epidemic and pandemic potential, which highlights the importance of screening studies of bat-derived viruses. This study investigates the prevalence and phylogenetic characteristics of coronaviruses in bat populations from the Rostov and Novosibirsk regions of Russia between 2021 and 2023. Utilizing PCR screening and sequencing, viruses belonging to the Alphacoronavirus genus were detected in several bat species, with prevalence rates ranging from 4.94% to 62.5%. Phylogenetic analysis of detected sequences revealed the presence of three subgenera: Pedacovirus, Myotacovirus, and Nyctacovirus. These sequences shared over 90% identity with alphacoronaviruses previously identified in bats across Northern Europe and Russia, underscoring the viruses’ wide geographic distribution and evolutionary connections. The results highlight the adaptability of alphacoronaviruses and the role of bat migratory behavior in their dispersal. The study underscores the importance of continuous monitoring and phylogenetic studies of bat-derived coronaviruses to better understand their ecological dynamics and potential zoonotic threats.